Autologous Breast Reconstruction after Mastectomy for Breast Cancer: A Systematic Review. Issue 3 (March 2022) - Saldanha, Ian J.; Broyles, Justin M.; Adam, Gaelen P.; Cao, Wangnan; Bhuma, Monika Reddy; Mehta, Shivani; Pusic, Andrea L.; Dominici, Laura S.; Balk, Ethan M.
Abstract : Background: Women undergoing autologous reconstruction (AR) after mastectomy for breast cancer and their surgeons must make decisions regarding timing of the AR and choose among various flap types. We conducted a systematic review to evaluate the comparative benefits and harms of (1) timing of AR relative to chemotherapy and radiation therapy, and (2) various flap types for AR. Methods: We searched Medline, Embase, Cochrane CENTRAL, CINAHL, and ClinicalTrials.gov for studies, from inception to March 23, 2021, without language restriction. We assessed risk of bias of individual studies and strength of evidence (SoE) of our findings using standard methods. Results: We screened 15, 936 citations. Twelve mostly high risk of bias studies, including three randomized controlled trials and nine nonrandomized comparative studies met criteria (total N = 31, 833 patients). No studies addressed timing of AR relative to chemotherapy or radiation therapy. Six flap types were compared, but conclusions were feasible for only the comparison between transverse rectus abdominus myocutaneous (TRAM) and deep inferior epigastric perforator (DIEP) flaps. The choice of either flap may result in comparable patient satisfaction with breasts and comparable risk of necrosis (low SoE for both outcomes), but TRAM flaps probably pose a greater risk of harm to the area of flap harvest (abdominal bulge/hernia and need for surgical repair) (moderate SoE). Conclusions: Evidence regarding details for AR is mostly of low SoE. New high-quality research among diverse populations of women is needed for the issue of timing of AR and for comparisons among flap types.